1999
DOI: 10.7863/jum.1999.18.7.475
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic involvement in hypereosinophilia: sonographic findings.

Abstract: Hypereosinophilic syndrome may cause eosinophil-related tissue damage to various organs. The purpose of this paper is to describe sonographic findings in 13 patients with hypereosinophilia in whom the liver was involved. The diagnosis in these 13 patients was based on liver biopsy in seven patients with bone marrow biopsy in six patients. Eight patients had hypereosinophilic syndrome and five patients had clonorchiasis. All 13 patients had mild to marked hepatomegaly. Seven of 13 patients showed multiple round… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Most radiologic reports, however, have focused on hypereosinophilic syndrome (5-9), a clinically distinct entity from FEN affecting patients with mild eosinophilia (1) such as those described in this study. As FEN is in most cases detected incidentally and usually manifests at CT as multiple hypoattenuating lesions, differentiation from metastasis has been a problem, particularly in patients with underlying extrahepatic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Most radiologic reports, however, have focused on hypereosinophilic syndrome (5-9), a clinically distinct entity from FEN affecting patients with mild eosinophilia (1) such as those described in this study. As FEN is in most cases detected incidentally and usually manifests at CT as multiple hypoattenuating lesions, differentiation from metastasis has been a problem, particularly in patients with underlying extrahepatic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the varied radiological appearance of hypereosinophilia with hepatic involvement (4-10), characterizing the hepatic lesions as small and focal. CT images demonstrated that these hepatic lesions were small, oval or round, showed low attenuation, and were scattered throughout the liver, especially in areas adjacent to the portal veins.…”
Section: Discussionmentioning
confidence: 99%
“…The number of foci was closely correlated with the percentage of eosinophils in peripheral blood, and decreased as the level of eosinophils decreased (7, 9). Ultrasound revealed that the foci were mostly hypo- (7, 10) but sometimes hyperechoic (10). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Korean authors have addressed the possible causes of eosinophilic infiltration such as idiopathic hypereosinophilia (1, 2, 4, 6) and malignant tumors through the tumor-associated eosinophilotactic factor (3, 5, 7-9), whereas some authors have offered no explanation (3, 9). Idiopathic hypereosinophilia is a grave disease that is characterized by persistent eosinophilia of 1,500 eosinophils/µL for more than six months, and death before six months due to congestive heart failure (14).…”
mentioning
confidence: 99%